Increased Chondrogenic Potential of Mesenchymal Cells From Adipose Tissue Versus Bone Marrow‐Derived Cells in Osteoarthritic In Vitro Models. Issue 6 (26th October 2016) - Pagani, Stefania; Borsari, Veronica; Veronesi, Francesca; Ferrari, Andrea; Cepollaro, Simona; Torricelli, Paola; Filardo, Giuseppe; Fini, Milena
Abstract : Primarily, to compare the behavior of human mesenchymal stem cells (MSCs) derived from bone marrow (hBMSCs) and adipose tissue (hADSCs) in an osteoarthritic (OA) microenvironment; secondly, to investigate the reaction of these cell types in two alternative in vitro culture systems, obtained by using TNFα and/or IL1β as inflammation mediators, or by using synovial fluid harvested by OA patients (OSF) to simulate the complex inflamed knee microenvironment. 3D micromass cultures of hBMSCs or hADSCs were grown in chondrogenic medium (CTR), in the presence of TNFα and/or IL1β, or synovial fluid from OA patients. After 1 month of culture, the chondrogenic differentiation of micromasses was evaluated by gene expression, matrix composition, and organization. Both hMSCs types formed mature micromasses in CTR, but a better response of hADSCs to the inflammatory environment was documented by micromass area and Bern score evaluations. The addition of OSF elicited a milder reaction than with TNFα and/or IL1β by both cell types, probably due to the presence of both catabolic and protective factors. In particular, SOX9 and ACAN gene expression and GAG synthesis were more abundant in hADSCs than hBMSCs when cultured in OSF. The expression of MMP1 was increased for both hMSCs in inflammatory conditions, but in particular by hBMSCs. hADSCs showed an increased chondrogenic potential in inflammatory culture systems, suggesting a better response of hADSCs in the OA environment, thus underlining the importance of appropriate in vitro models to study MSCs and potential advantages of using these cells for future clinical applications. J. Cell. Physiol. 232: 1478–1488, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Primary objective of this paper was to compare the behavior of human mesenchymal stem cells (MSCs) derived from bone marrow (hBMSCs) and adipose tissue (hADSCs) in an osteoarthritic (OA) microenvironment; secondly, to investigate the reaction of these cell types in two alternative in vitro culture systems, obtained by using TNFα and/or IL1β as inflammation mediators, or by using synovial fluid harvested by OA patients (OSF) to simulate the complex inflamed knee microenvironment.